Atrial myxoma masquerading as Takayasu's arteritis. (4th November 2014) - Fung, Kenneth; Edmondson, Stephen; Wald, David S
Lesson: We describe the case of a 48-year-old woman whose atrial myxoma was mistaken for vasculitis. The case report highlights the reasons why these two disorders may become confused, the dangers of initiating the wrong treatment and a simple means of avoiding misdiagnosis.